A Swedish national forest programme – participation and international agreements - Ahlgren, Anna (2014)
Sweden is in the initial phase of forming a national forest programme (nfp). The establishment of an nfp has been evoked by international policy developments and a national debate questioning Swedish forestry and forest policy. National forest programmes are participatory processes for the development and implementation of forest-related policies and international commitments. Hence, the aim of this master thesis is to assess the stakeholders’ acceptance of participation and integration of international issues within the Swedish national forest programme. Based on the concept of governance, this study’s research questions focused on the integration of international issues and the scope and depth of participation in an nfp. To answer the research questions a literature review of European nfps and interviews with Swedish forest actors were performed.